Bacteriophage WO Can Mediate Horizontal Gene Transfer in Endosymbiotic Wolbachia Genomes - Wang, Guan H.; Sun, Bao F.; Xiong, Tuan L.; Wang, Yan K.; Murfin, Kristen E.; Xiao, Jin H.; Huang, Da W. (Frontiers in Microbiology, 2016)
Phage-mediated horizontal gene transfer (HGT) is common in free-living bacteria, and many transferred genes can play a significant role in their new bacterial hosts. However, there are few reports concerning phage-mediated HGT in endosymbionts (obligate intracellular bacteria within animal or plant hosts), such as Wolbachia. The Wolbachia-infecting temperate phage WO can actively shift among Wolbachia genomes and has the potential to mediate HGT between Wolbachia strains. In the present study, we extend previous findings by validating that the phage WO can mediate transfer of non-phage genes. To do so, we utilized bioinformatic, phylogenetic, and molecular analyses based on all sequenced Wolbachia and phage WO genomes. Our results show that the phage WO can mediate HGT between Wolbachia strains, regardless of whether the transferred genes originate from Wolbachia or other unrelated bacteria.